Volvulus of Gravid Uterine Horn in a Pregnant Cat: First Report in India - J Parmar, Jignesh; B Patel, Urja; R Mecvan, Arnold; I Shah, Aditya; K Patel, Shital; S Prajapati, Ankit; K Hadiya , Kamlesh (Indian Journal of Veterinary Sciences and Biotechnology, 2025)
Torsion is the twisting of an organ around its own axis, while volvulus is the rotation of an organ around its  mesenteric axis. Uterine torsion is defined as the twisting of  a uterine horn or uterine body about the longitudinal axis  (Roberts, 1971). Uterine torsion is an uncommon complication  of pregnancy in the cat (Riyard et al., 2000). Uterine torsion  is life threatening both for the pregnant cat and fetuses, and  its aetiology is unclear (Tohumcu et al., 2021), but loosened  uterine ligaments, uterine contractions, fetal movements,  maternal physical activity during pregnancy are the possible  predispositions for the torsion (Biller and Haibel, 1987). There  are published reports on the uterine torsion, but a very few  reports of uterine twisting at the base of the uterine horn and  ovarian end causing volvulus of uterine horn are available in  cats (Thilagar et al., 2005). This paper presents a first report  of very rare volvulus of gravid uterine horn in a pregnant  cat in India.
Keywords: Torsion; twisting; organ; volvulus; rotation